The Concept of Al-Qur'an on Teacher Competency (Thematic Analysis of Surah Al-Qalam Verses 1-4) - Rusi yan (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
This study aims to know about the competence of teachers, and what the concept of the Qur'an about the competence of teachers in Surat Al-Qalam Verses 1 - 4. This research is a library review (library research) which is qualitative descriptive, using documentation techniques in data collection. While the method of data analysis used is the tafsir maudlu'iy method. The results show that: Firstly, the qualities that an educator must have are (a) zuhud not putting matter and teaching because of seeking God's mercy; (b) to cleanse his body, away from sin and guilt, to escape from great sin, ridicity, envy, hostility, strife and other disgraceful nature; (c) Ikhlas in the work; (d) forgiving; (e) loving his disciples just as he loved his own son; (f) knowing the student's nature; (g) mastering subjects; (h) have competence in the ways of teaching. Second, the competence that must be owned by the teacher according to the Qur'an letter Al-Qalam verses 1-4 is to have the personality as exemplified by the Prophet Muhammad SAW, master and utilize information technology and communications for self-development and science and have the ability paper for the development of science and communication media with others.Keywords: Competence of teachers, Concepts of the Qur'an, Tafseer of al-Alaq